Choice of Cause in Cause-Related Marketing - Robinson, Stefanie Rosen; Irmak, Caglar; Jayachandran, Satish (Journal of Marketing, 2012)
Spurred by the consumer demand for companies to be socially responsible, cause-related marketing (CM), in which fund raising for a cause is tied to purchase of a firm's products, has become popular in recent years. The authors demonstrate the conditions in which CM campaigns that allow consumers to choose the cause that receives the donation lead to greater consumer support than those in which the company determines the cause. They show that choice in this context is helpful as long as it increases consumers’ perception of personal role in helping the cause. Specifically, allowing consumers to select the cause in a CM campaign is more likely to enhance perceived personal role and, thus, purchase intentions (1) for those consumers who are high (vs. low) in collectivism and (2) when the company and causes have low (vs. high) perceptual fit. Finally, the authors show that under certain conditions, choice may have a negative impact on perceived personal role and consumer support of CM campaigns.